Contextualising а Lexicon аt а Crossroads - William R. Veder (Slavia Meridionalis, 2025)
This article is a review of a study entitled Преславските лексикални маркери [The Preslav Lexical Markers], authored by Yavor Miltenov (Sofia, 2024, 232 pp.).